Synthesis and Characterization of chiral Cu(II) and Ni(II) complexes of Amino Acid Derived Ligands and Aniline Based polymers with Functional Group - Koner, Rik Rani (My University, 2009)
This thesis represents our effort to rationalize the formation of octanuclear assembly of Cu(II) as well as the exploration of the coordination chemistry of amino acid derived reduced Schiff base ligands by systematically variation of amino acids, solvent, external ligand, substitution of ligand on aromatic ring, different metal/ligand ration and metal ion. ..
Ray, Manabendra
Keywords: CHEMISTRY